IMPLEMENTASI PENGGUNAAN APLIKASI ALPEKA DALAM PENGELOLAAN DANA BOS DI SD NEGERI SE-KECAMATAN SENAPELAN KOTA PEKANBARU - Abdul Mukti; Mahdum Mahdum; Gimin Gimin (Universitas Riau, 2021)
This research aims to analyze the Implementation of ALPEKA Application Usage in the Management of BOS Fund in SD Negeri Se-Kecamatan Senapelan Pekanbaru City, which refers to: (1) Goals; (2) managers; (3) facilities and infrastructure; (4) Implementation; (5) Evaluation of the use of ALPEKA applications. Implementation of ALPEKA application is analyzed from: (1) communication, (2) resources, (3) executor attitude, and (4) bureaucratic structure, based on the policy implementation model according to Edward. This study used descriptive qualitative method. Data is taken through interviews, observation, and documentation.The results showed that: (1) Information received in the process of managing the BOS funds in SD Negeri as a sub-district senapelan Pekanbaru city has not been fully on time. (2) Resources, such as human resources, hardware resources, software resources and data management processes into information greatly assist the management of BOS funds. Because resources greatly affect the implementation of the use of ALPEKA applications in the management of BOS funds in SD Negeri in Senapelan sub-district Pekanbaru city. By using ALPEKA applications in the management of BOS funds will be more effective and efficient when compared with manuall.